Visualization of pleural fissures in infants on computed tomography - Andrew Phelps; Cynthia Tan; Saveen Ahuja; Dean Kolnick; Jesse Courtier; John D MacKenzie (BMJ Publishing Group, 2019)
Purpose For infants with prenatally detected lung lesions, a chest CT is performed prior to surgery. The chest CT is performed as close to the surgery date as possible, because it is presumed that the visualization of lung fissures would be poor in the immediate neonatal setting. However, this presumption has never been formally studied. The purpose of this study is to assess differences in lung fissure visualization on chest CT in different infant age groups.Methods This was a retrospective study of clinically indicated chest CT approved by the institutional review board performed in infants of different ages. The visibility of pleural fissures was subjectively assessed by three pediatric radiologists who were blinded to age group.Results In the 0-2 months age group, 80% of all fissure segments were visible versus 92% in the 5-6 months group (p=0.04) and 95% in the 7-9 months group (p=0.01).Conclusions The ability to visualize pleural fissures on CT increases with infant age. This observation should be taken into consideration when choosing the optimal timing of preoperative CT for asymptomatic congenital lung lesions.